Perfil dos biomarcadores plasmáticos de morbidade na mielopatia associada ao HTLV- 1/paraparesia espástica tropical (HAM/TSP) - Ana Lucia Borges Starling (2016)
This study aimed at evaluating the biomarkers that may indicate the evolution from the state of asymptomatic carrier (AC) to HTLV-1-associated myelopathy/tropical spastic paraparesis(HAM/TSP) based on the serum biomarkers of different clinical stages of HTLV-1-infection. A panel of serum biomarkers was evaluated in samples of 21 blood donors and 87 HTLV-1- infected individuals: 27 AC, 32 putative HAM/TSP (pHAM/TSP) and 28 HAM/TSP. The analyses of cumulative curves and molecular signatures pointed out that HAM/TSP presented a pro-inflammatory profile mediated by CXCL10/LTB-4/IL-6/TNF-/IFN-, barely counterbalanced by the regulatory cytocines IL-4/IL-10. The group AC presented a strongly pro-inflammatory/regulatory net, with IL-4/IL-10 playing a central role. Therefore, an immunologic signature of controlled inflammation was characteristic of AC and another of uncontrolled inflammation was typical of HAM/TSP. The biomarkers IL-6 and CystLT were crucial to classify the individual in the spectrum of the disease. These results allowed theconstruction of an algorithm to discriminate AC, pHAM and HAM/TSP based on the selected biomarkers: IFN-, TNF-, IL-10, IL-6, IL-4 and CysLT. Based on the logistic regression, a tree of decision was proposed as a possible strategy to predict the evolution from asymptomatic infection to HAM/TSP, which may be very important in terms of follow-up and future therapeutic decisions.